The representative Utilities of individual preference chain - Morkeliūnas, A. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. И. Моркелюнас. Репрезентативные полезности индивидуальных профилей предпочтенияA. Morkeliūnas. Individualių vertinimo profilių reprezentatyviniai naudingumai